TREATMENT OF VAGINAL CANDIDIASIS CHRONIC RECURRENT VAGINAL CREAM TIOCONAZOLE WITH THE 2% - Gonzáles Ender, Rodolfo (2015)
27 patients with chronic recurrent vaginal candidiasis type were treated intravaginally for 3 days with Tioconazole vaginal cream 2%. In this group the microbiological negativization was achieved in 74.1% of cases in the short-term assessment and in 63% of cases in the long term; No patient was lost to follow-up until 35 days post treatment. Of the 17 patients with negative cultures up to 35 days post-treatment follow-up, which were re-evaluated between 60-80 days after completion of treatment, two patients were lost and 12/15 (80%) continued. It is microbiologically negative. Consequently, it is our impression that the three cases should be considered positivaron reinfection. From a clinical point of view and the patients' symptoms and signs reversed quickly, especially during the first 5 days after starting treatment. When symptoms recur, it is most likely that the infection is turning or patients were reinfected. The tolerance should be considered remarkably good, no undesirable effects were detected.